Pandangan Para Ahli Bahasa tentang Bahasa Serapan dalam al-Quran - Mahyudin Ritonga (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2015)
This article explains some words in the Qur’an which are believed to have been taken from non Arabic word. Whether or not the Quran comprises non Arabic words, and whether the Qur’an has Arabized some foreign an non Arabic words has been stimulated debate among scholars. Some ulama (Islamic scholars) believe that the Quran only embraces Arabic word. But some others argue that there are some words in the Qur’an which are not recognized in Arabic language, and they also suggests that this is a kind of weakness of the Qur’an. This article focuses on how arabisation process has taken place furing the formation of the Qur’an as a corpus